Investigating invertebrate biodiversity around large wood: taxonomic vs functional metrics - Magliozzi, Chiara; Meyer, Albin; Usseglio-Polatera, Philippe; Robertson, Anne; Grabowski, Robert C. (Springer, 2020)
Large wood is a key component of river channels that affects numerous hydrological, physical and geomorphological processes. It promotes a diversity of benthic habitats in-channel and has shown to support more abundant and diverse benthic macroinvertebrate assemblages in previous ecological studies. However, the effects of large wood on the structural and functional diversities of hyporheic invertebrates are less well studied, and simultaneous examination of these diversity metrics on hyporheic and benthic compartments of the stream bed has not been conducted previously. Therefore, this study investigates the taxonomic and functional diversities of hyporheic and benthic invertebrate assemblages around natural accumulations of large wood in a British lowland river. Taxonomic and functional diversities were partitioned (into alpha, beta, and gamma diversities) and examined in reaches with and without large wood (control). We found that functional diversity is often decoupled from taxonomic diversity, demonstrating a functional redundancy of the macroinvertebrate assemblage for both hyporheic and benthic zones. Moreover, the highest functional variability at alpha-scale was observed in large wood habitats, which suggests that taxonomic diversity is enhanced by the small-scale environmental heterogeneity around large wood. To this end, this study contributes empirical evidence of functional and structural responses of invertebrates to large wood accumulation. Such information could be used to better understand the ecological implications of restoration works in lowland rivers and guide more effective management strategies
Keywords: Rao index; Meiofauna; Macrofauna; River; Hyporheic zone; Diversity partitioning